RICK/RIP2 is a NOD2-independent nodal point of gut inflammation. (27th May 2019) - Watanabe, Tomohiro; Minaga, Kosuke; Kamata, Ken; Sakurai, Toshiharu; Komeda, Yoriaki; Nagai, Tomoyuki; Kitani, Atsushi; Tajima, Masaki; Fuss, Ivan J; Kudo, Masatoshi; Strober, Warren
Abstract: Previous studies have shown that inhibition of receptor-interacting serine/threonine kinase (RICK) (also known as RIP2) results in amelioration of experimental colitis. This role has largely been attributed to nucleotide-binding oligomerization domain 2 (NOD2) signaling since the latter is considered a major inducer of RICK activation. In this study, we explored the molecular mechanisms accounting for RICK-mediated inhibition of inflammatory bowel disease (IBD). In an initial series of studies focused on trinitrobenzene sulfonic acid (TNBS)-colitis and dextran sodium sulfate (DSS)-colitis we showed that down-regulation of intestinal RICK expression in NOD2-intact mice by intra-rectal administration of a plasmid expressing RICK-specific siRNA was accompanied by down-regulation of pro-inflammatory cytokine responses in the colon and protection of the mice from experimental colitis. Somewhat surprisingly, intra-rectal administration of RICK-siRNA also inhibited TNBS-colitis and DSS-colitis in NOD2-deficient and in NOD1/NOD2-double deficient mice. In complementary studies of humans with IBD we found that expression of RICK, cellular inhibitor of apoptosis protein 2 (cIAP2) and downstream signaling partners were markedly increased in inflamed tissue of IBD compared to controls without marked elevations of NOD1 or NOD2 expression. In addition, the increase in RICK expression correlated with disease activity and pro-inflammatory cytokine responses. These studies thus suggest that NOD1- or NOD2-independenent activation of RICK plays a major role in both murine experimental colitis and human IBD. Abstract : RICK/RIP2 can mediate NOD2-independent gut inflammation